11 Using in-situ simulation as a tool to improve learning from serious incidents. (17th November 2016) - Blackmore, A; Madaiah, S; Purva, M
Abstract : Objective: The aim of this project was to design and trial a way of investigating the root cause of serious incidents, while simultaneously allowing institutional learning to be led by the staff in the area involved. This would increase participation in the process of root cause analysis and quality improvement. Method: We recreated the circumstances of a Serious Incident in an in-situ simulation session in the bay where the incident occurred. Participants were a patient (actor) and a doctor and nurse from the same ward. Observers included 14 other ward staff, watching via video link. We asked each participant and observer to fill in pre- and post session questionnaires. The session ran in real-time with group feedback using an advocacy with enquiry model. Results: Feedback was overwhelmingly positive, many more staff became aware of the incident than would have done via the usual process. Specific questions highlighted that: Certain team members didn't feel that EWS were useful The understanding of the escalation policy was poor The majority believed that 80–85% of EWS as calculated by them were accurate – this highlighted the concept of an 'illegal normal' within the group The group discussion allowed all members of the team to engage with the root cause analysis and develop collective targets. The ward now have a self-generated improvement project to improve care of the deteriorating patient. Conclusion: Using in situ simulation to learn from a serious incident has potential to increase engagement and ensure the lessons learned from the incident are communicated more effectively with the frontline staff. Staff felt ownership of the process and engagement with the root cause analysis was greater than would usually happen during an investigation. Where staff were able to identify learning points themselves, there was greater willingness to address these points than when given proscriptively.